Pengaruh Operating Cash Flow, Operating Capacity, Sales Growth, dan Leverage Terhadap Financial Distress - Silfi Alfiani,; Regina Jansen Arsjah, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the relationship between operating cash flow, operating capacity, sales growth, and leverage on financial distress in cyclical consumer sector companies in Indonesia during the 2021-2023 period. Using a quantitative approach and panel data regression model, this study aims to identify operational and structural indicators that play a role in reflecting the financial condition of companies. The findings show that operating cash flow has a positive effect on financial distress, contrary to the initial assumption that higher cash flow reflects financial resilience. On the other hand, operating capacity and sales growth have no effect on financial distress. Leverage shows a negative effect on financial distress, indicating that firms with higher levels of debt in certain contexts can better manage financial stress. These results highlight the importance of understanding operational dynamics and capital structure contextually in an effort to anticipate potential corporate financial crises.